IMPLEMENTASI KEBIJAKAN PENANGGULANGAN BENCANA BANJIR DI PERUMAHAN BATARANILA DESA HAJIMENA KECAMATAN NATAR KABUPATEN LAMPUNG SELATAN - Suryandari, Kris Ari; Makhya, Syarief; Budiono, Pitojo; Amantha, Goestyari Kurnia (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2024)
Flooding is the submergence of land by water due to heavy rainfall that increases water volume. This situation has also occurred in Bandar Lampung City, which has recently experienced flooding. The disaster affects not only Bandar Lampung but also nearby areas, such as the Bataranila Housing in Hajimena Village, Natar district, South Lampung Regency, which directly borders Bandar Lampung City. This study aims to examine the implementation of flood disaster management policies in Bataranila Housing, Hajimena Village, Natar district, South Lampung Regency. The study employs the policy implementation theory of Van Meter and Van Horn, which includes six indicators: Policy Goals and Objectives, Resources, Inter-Organizational Communication, Characteristics of Implementing Organizations, Implementer Disposition, and Social, Economic, and Political Conditions. This research is a descriptive qualitative study. The findings show that the Village Government has implemented policies according to its capacity and capability, as evidenced by the coordination between agencies, allowing for swift action in emergencies. Furthermore, the implementer disposition indicator reveals that the Village Government shows strong concern for flood issues by advising the community against littering and encouraging environmental conservation. However, limitations in authority and resources allocated for flood management persist, as disaster management is not yet prioritized in the village’s programs, resulting in no specific funding allocation